Carbapenem-resistant Enterobacteriaceae on a cardiac surgery intensive care unit: successful measures for infection control. Issue 1 (September 2016) - Abboud, C.S.; de Souza, E.E.; Zandonadi, E.C.; Borges, L.S.; Miglioli, L.; Monaco, F.C.; Barbosa, V.L.; Cortez, D.; Bianco, A.C.; Braz, A.; Monteiro, J.
Summary: Background: Carbapenem-resistant Enterobacteriaceae (CRE) cause surgical site infections (SSIs) in intensive care units (ICUs). This study aimed to evaluate the impact of intervention and control measures to reduce CRE colonization and infection rates among patients in the ICU of a cardiac surgery hospital following a CRE outbreak. Methods: An observational study of the pre- and postintervention status of a cohort of colonized or infected patients in the postoperative adult cardiac surgery ICU was performed between April 2013 and December 2014. As well as the usual measures of screening and cohort nursing, the control measures were enhanced during the intervention period by providing alcohol gel at the bedside, daily bathing with no-rinse 2% chlorhexidine-impregnated wash cloths, and disinfection of surfaces around the patient three times per day. Results: The rates of CRE colonization ( P <0.001), primary central-line-associated bloodstream infections ( P <0.002) and SSIs ( P < 0.003) decreased significantly during the postintervention period. Conclusion: The implemented measures were effective in controlling colonization and infection with CRE in the cardiac surgery ICU.